THE EFFECT OF INDEPENDENT COMMISSIONERS, COMPANY SIZE AND PROFITABILITY ON TAX AVOIDANCE IN COMPANIES LISTED IN THE IDX80 INDEX OF THE INDONESIA STOCK EXCHANGE - Ardiansyah, Muklas Nur; Zulaihati, Sri; Mardi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this study is to investigate the impact of independent commissioners, company size, and profitability on tax avoidance in companies listed on the Indonesia Stock Exchange's IDX80 index. The research method employed is a quantitative research method using correlational research. The IDX80 companies listed on the Indonesia Stock Exchange in 2019 - 2020 comprise the population in this study, with a total of 80 companies. The information was gathered by gathering the annual financial statements of the IDX80 companies from the Indonesia Stock Exchange website. In this study, the affordable population consisted of 57 IDX80 enterprises, with a sample of 50 companies drawn using a simple random sampling technique based on the Isaac and Michael formula. Data collection methods based on documentary techniques. Descriptive statistics, analysis requirements testing, classical assumption testing, multiple linear regression testing, and hypothesis testing are the data analysis techniques used. According to the findings of this study, independent commissioners have no effect on tax evasion, company size influences tax avoidance, and profitability has no effect on tax avoidance. The coefficient of determination in this study is 6%, indicating the potential of independent commissioners, company size, and profitability to influence tax avoidance, while the remainder is influenced by other factors that were not investigated.